Permanently stationed bacteriobots for surveillance and elimination of nascent tumours - Praneshwar Eswaran (Future Healthcare Journal)
Introduction: Could a nanorobot be permanently embedded within the body to continually detect and eliminate cancer cells at their earliest stages? Delay in cancer diagnosis is an emergency issue in the UK and has various challenging consequences for patients, including increased mortality.1 Additionally, current systemic therapies for treating cancer have been associated with various side effects.2 Nanorobots are an emerging targeted therapy for selectively detecting and eliminating cancer cells, but their role has largely been limited to drug delivery systems.3 To enable early detection and elimination of cancer cells, I present a novel theoretical bacteriobot model that remains stationed within high-risk tissues in patients with high-penetrance cancer mutations. The bacteriobot would continually monitor the tissue for cancer cells and eliminate them, significantly reducing cancer incidence in patients with high-penetrance cancer mutations. Materials and methods: A permanently stationed nanorobot raises important considerations about biocompatible materials, design, energy source, long-term viability, safety and immune system interactions. Additionally, its ability to target and eliminate cancer cells raises questions about its biosensors and cancer cell-targeting mechanism. This study addresses these questions by presenting the application of such a nanorobot specifically for BRCA-mutated breast cancer. An extensive literature review was conducted to identify a suitable nanorobot, modifications for detecting BRCA-mutated cancer cells, mechanisms for their elimination and strategies to ensure patient safety. Results and discussion: From the literature review, bacteria were identified as the most suitable nanorobot due to their proliferative capacity and self-sustaining ability, allowing them to permanently remain within the tissue.4 Analysis of breast tissue microbiota identified Lactobacillus as a suitable bacterium for the bacteriobot due to its immunocompatibility and bioengineering potential, enabling its residence within the breast tissue.5 To equip the bacteriobot with capability to detect cancer cells, its highly specific and sensitive intercellular peptide signaling receptors were modified to identify BRCA-mutated breast cancer-specific peptides.6 In a profiling study, certain members of KNG1 and C3f protein families were identified as unique biomarkers expressed by BRCA-mutant cancer cells.7 Upon detecting these specific peptides, the bacteriobot, using its two-component system, induced tumour elimination via CD47 blockade. This was achieved by modifying the bacteria to produce and release CD47 antagonist nanobodies, which allow phagocytosis of the tumour cell, effectively eliminating it.8 To ensure patient safety, the bacteriobot was engineered with a quorum-sensing lysis mechanism to prevent overgrowth, while its production of CD47 antagonist nanobodies was regulated by riboswitches to minimise unintended toxicity (Fig 1). Conclusion: While the specific example of BRCA-mutant breast cancer has been used here to elucidate the application of this bacteriobot, the principle behind it is applicable to any type of cancer. Such an approach would revolutionise cancer treatment by significantly reducing cancer incidence and would transform targeted therapy by optimising efficacy while minimising adverse effects. While the basis of the bacteriobot is evidence based and derives principles from existent nanorobot models, experimental validation is necessary to evaluate its feasibility. Thus, this study paves the way for further research into its applications.